Keteladanan Guru Dalam Pembiasaan Karakter Sosial Siswa Taman Kanak-Kanak Berciri Islam - Ngaisah, Siti; imroatun, Imroatun; Ramadani, Dede Riska; Muthmainnah, Muthmainnah (Universitas Cokroaminoto Yogyakarta, 2023)
This study aims to find out how the implementation of the teacher's example in the formation of the character of social care and discipline in children aged 5-6 years in TKIB, Pandeglang Regency, to find out the various characteristics of children in TKIB, Pandeglang Regency, and to find out the teacher's obstacles in forming character social care and child discipline. The method used in this research is descriptive qualitative with data collection tools namely observation, interviews, documentation and triangulation, in this study the subjects of the research were children aged 5-6 years. The results of the study show that the implementation of the teacher's example in shaping the character of social care and discipline in children is urgently needed. This can be seen from the way the teacher sets a good example by implementing the character values of social care and discipline in daily learning activities at school. However, there are several obstacles faced by teachers regarding the formation of social care and child discipline characters such as time constraints where teachers do not have much time at school to continue implementing these things. In addition to the time factor, the child's personal circumstances are also one of the obstacles in forming the socially caring and disciplined character of children through the implementation of the teacher's example. So it can be concluded that the implementation of the teacher's example is very influential in shaping the social care and discipline character of children aged 5-6 years in TKIB, Pandeglang Regency, Banten.